Illness and injury in athletes during the competition period at the London 2012 Paralympic Games: development and implementation of a web-based surveillance system (WEB-IISS) for team medical staff. Issue 7 (28th March 2013) - Derman, Wayne; Schwellnus, Martin; Jordaan, Esme; Blauwet, Cheri A; Emery, Carolyn; Pit-Grosheide, Pia; Marques, Norma-Angelica Patino; Martinez-Ferrer, Oriol; Stomphorst, Jaap; Van de Vliet, Peter; Webborn, Nick; Willick, Stuart E
Abstract : Background: In this study we describe (1) the implementation of a novel web-based injury and illness surveillance system (WEB-IISS) for use by a team of physicians at multisport events and (2) the incidence and characteristics of injuries and illness in athletes during the London 2012 Paralympic Games. Methods: Overall, 3565 athletes from 160 of the 164 participating countries were followed daily over a 14-day period, consisting of a precompetition period (3 days), and a competition period (11 days) (49 910 athlete-days). Daily injury and illness data were obtained from teams with their own medical support (78 teams, 3329 athletes) via the WEB-IISS, and without their own medical support through the London Organising Committee of the Olympic Games and Paralympic Games database (82 teams and 236 athletes). Results: There were no differences between incidence rates (IR) of injury and illness, or between the precompetition and competition periods. The IR of injury during the competition period was 12.1/1000 athlete-days, with an incidence proportion (IP) of 11.6% (95% CI 11.0% to 13.3%). Upper limb injuries (35%), particularly of the shoulder (17%) were most common. The IR of illness during the competition period was 12.8/1000 athlete-days (95% CI 12.18 to 1421), with an IP of 10.2%. The IP was highest in the respiratory system (27.4%), skin (18.3%) and the gastrointestinal (14.5%) systems. Conclusions: During the competition period, the IR and IP of illness and injury at the Games were similar and comparable to the observed rates in other elite competitions. In Paralympic athletes, the IP of upper limb injuries is higher than that of lower limb injuries and non-respiratory illnesses are more common.